Adsorption enhancement of hazardous odor gas using controlled thermal oxidation of activated carbon. (20th March 2023) - Phyo, Sooyeol; Kim, Sooyeon; Lee, Heehyeon; Han, Sang Soo; Oh, Youngtak; Lee, Jiwon
Abstract: Nitrogen-containing odorous compounds (NOCs) such as ammonia, ethylamine, dimethylamine, and trimethylamine (TMA) have potentially adverse effects on the environment and human health. An efficient and simple strategy for NOC removal is necessary. Herein, thermally dried activated carbon adsorbents (TDACs) were prepared, and their surfaces were subjected to controlled thermal oxidation at 50, 100, and 200 °C. The resulting TDACs exhibited micropore-intensive porous structures with different specific surface areas (SSA) (135–562 m 2  g −1 ) and demonstrated 2–38 times higher NOC-adsorption capacity (12.35–102.92 mg g −1 ) than that of pristine AC in a fixed-bed breakthrough test. Comprehensive surface characterization revealed a correlation between the thermal oxidation conditions and corresponding SSAs. Density functional theory calculations revealed that multidentate hydrogen bonding potential prevails over proton affinity in determining the NOC-adsorption trend. The fractal-like kinetics of the classical adsorption fitting for the TDACs suggested a heterogeneous adsorption behavior (R 2  = 0.9998). A competitive adsorption test for the TDACs using a binary mixture of TMA and benzene demonstrated that TMA is favorably adsorbed over benzene and that the co-adsorption process involves a roll-up effect. This study demonstrates that NOC adsorption on TDACs can be controlled via a thermal oxidation strategy, which affords adsorbents with high reusability and adsorbate selectivity. Graphical abstract: Image 1 Highlights: Thermal oxidation created oxygen functionalities on activated carbon surface NOC adsorption on TDACs was more homogeneous than that on pristine AC Multidentate H-bonding potential of NOCs enhanced their adsorption capacity Regeneration efficiency of TDAC 50 was 95% even after 10 regeneration cycles Co-adsorption of benzene and trimethylamine showed "roll-up" effect